ANALISIS KEBIJAKAN APBD DARI ASPEK IMPLEM ENTAS! DIBERLAKUKAN OTONOMI DAERAH (STUDI KASUS PEMKOT YOGYAKARTA DIY 1992 - 2002) - Agus Tri Basuki (Universitas Muhammadiyah Yogyakarta, 2010)
By autonomy, most of resources that managed by central government becomes managed by local government. By decentralization, services to the society will be more efficient and effectively. This paper will analyze how far the response of local income because of change in Gross Regional Domestic Product (GRDP,) and also the ability of regional finance in regional autonomy era. The result of this paper shows that the coefficient of elasticity of regional income more than one, it means that if Gross Regional Domestic Product (GRDP) increase one percent, it will increases local income more than one percent. The role of domestic income to local income decrease, it means that the local government has to look for a forward alternative how lo increases the role of domestic income to local income.